2007
DOI: 10.1007/s11019-007-9106-y
|View full text |Cite
|
Sign up to set email alerts
|

East meets West: Cross-cultural perspective in end-of-life decision making from Indian and German viewpoints

Abstract: Culture creates the context within which individuals experience life and comprehend moral meaning of illness, suffering and death. The ways the patient, family and the physician communicate and make decisions in the end-of-life care are profoundly influenced by culture. What is considered as right or wrong in the healthcare setting may depend on the socio-cultural context. The present article is intended to delve into the cross-cultural perspectives in ethical decision making in the end-of-life scenario. We at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 25 publications
2
47
0
1
Order By: Relevance
“…Several scholars have highlighted the historic connectedness between spirituality and healthcare both in the western and eastern traditions [53][54][55]. The root of this relationship is often located in the understanding of illness as a "spiritual event" that "grasps persons by the soul and by the body and disturbs them both" [38].…”
Section: Methodsological Issues In the Study Of Spiritualitymentioning
confidence: 99%
“…Several scholars have highlighted the historic connectedness between spirituality and healthcare both in the western and eastern traditions [53][54][55]. The root of this relationship is often located in the understanding of illness as a "spiritual event" that "grasps persons by the soul and by the body and disturbs them both" [38].…”
Section: Methodsological Issues In the Study Of Spiritualitymentioning
confidence: 99%
“…This kind of legislation would be unthinkable in countries such as India where the family and the treating physician play a much larger role in the medical decision making process than in the West (Raj 2012;Seetharam and Zanotti 2009;Senarath and Gunawardena 2009;Chattopadhyay and Simon 2008;Chaturvedi 2008). Partially, this intervention of others in decision making can be explained by paternalism.…”
Section: Teaching Socio-culturally Appropriate Ethical Theoriesmentioning
confidence: 99%
“…People tend to get involved in the decisions driven by concern not only for the patient but also for all other people who may be affected by the treatment decision. Family members of patients often withhold medical information from a patient with advanced disease, because they are afraid that knowledge about the diagnosis and prognosis will destroy the patient's hope and in this way accelerate the disease progress or complicate emotional wellbeing (Chattopadhyay and Simon 2008;Raj 2012). But oftentimes, when treatment decisions are made the wellbeing of the family is also at stake.…”
Section: Teaching Socio-culturally Appropriate Ethical Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…While promoting an understanding of spirituality based on patient and staff perspectives, these studies have highlighted the need for unpacking the historical and cultural meanings of concepts that shaped the understanding of spirituality in the Indian context. Studies have demonstrated that Indian philosophical and religious concepts such as Karma , dharma , ātman and the notion of rebirth, for example, have a considerable influence on Indian perceptions of spirituality at the end of life (Chattopadhyay & Simon, 2008; Desai, 1988). Establishing an overview of the philosophical concepts is crucial for understanding their influence on perceptions of spirituality.…”
mentioning
confidence: 99%